2017
DOI: 10.1038/srep41683
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphisms of the ADIPOQ gene and hypertension risk: a systematic and meta-analysis

Abstract: ADIPOQ gene polymorphisms have been indicated to be associated with hypertension; however, published studies have reported inconsistent results. Eligible studies were retrieved by searching the PubMed, Embase and China National Knowledge Infrastructure databases. The case group consisted of patients with hypertension, and the control group consisted of subjects with normal blood pressure. Based on eleven published articles, involving 4837 cases and 5618 controls, the pooled results from rs2241766 polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…Heterogeneity was evaluated by Q statistic (significance level of P < 0.1) and I 2 statistic (greater than 50% as evidence of significant inconsistency). To adjust for multiple comparisons, we applied the Bonferroni method to control the false discovery rate (FDR) [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was evaluated by Q statistic (significance level of P < 0.1) and I 2 statistic (greater than 50% as evidence of significant inconsistency). To adjust for multiple comparisons, we applied the Bonferroni method to control the false discovery rate (FDR) [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The four remaining variants were associated with higher abundance of a unique OTU: the SNP rs266729 in ADIPOQ was associated with an OTU related to Subdoligranulum variabile; the intronic SNP rs2975760 in the gene encoding calpain-10 (CAPN10) with an OTU related to Lachnospira; the intronic SNP rs709149 in the gene encoding peroxisome proliferator-activated receptor gamma (PPARγ) with an OTU related to Coprococcus eutactus; and the intronic SNP rs7903146 in the gene encoding transcription factor 7-like 2 (TCF7L2) with an OTU related to Ruminococcus gauvreauii (Figure 1; Table S2). Most of these variants and microbiota were associated with impaired cardiometabolic health 6,30,44,54,67 but the limited number of associations detected here requires further confirmation.…”
Section: Energy Metabolismmentioning
confidence: 77%
“…The synonymous SNP rs2241766 in the gene encoding adiponectin (ADIPOQ) has been highly studied and recent meta-analyses have associated it with CMS, 53 hypertension, 54 and coronary artery disease. 55 We found it was associated with a proinflammatory state (higher levels of highsensitivity C-reactive protein: hs-CRP), as well as to increased abundance of several gut microbiota, including the same OTUs of Coprococcus, Prevotella stercorea, Ruminococcus albus and Ruminococcus callidus that were associated with variants at NOD2 and TLR5 (Figure 1; Table S2).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…Further, there might be an interaction between BMI and HDL-C, which showed that the HDL-C was higher among participants with hypertension than those with normal BP in almost all BMI groups except those with normal BMI. Besides, other confounding risk factors 27 , 28 that were not under our consideration might also have impacts on this association.…”
Section: Discussionmentioning
confidence: 99%